A comparative Analysis Altman (Z-Score) Revision and Springate (S-Score) Model in Predicting Financial Distress in the Manufacturing Company - Indonesia Stock Exchange - Emmelia Tan; Tri Aji Wibisana (Journal of Research in Business, Economics, and Education, 2020)
This study aims to examine the effect of the Altman (Z-Score) Revision model and the Springate (S-Score) model and determine the better and more precision model in predicting financial distress in the manufacturing company on the Indonesia Stock Exchange. The data analysis technique used is logistic regression to prove the study hypothesis. Based on the results testing, can be concluded: 1) Altman Model (Z-Score) Revision :Working Capital to Total Asset, Retained Earning to Total Asset, and EBIT to Total Aset no effect on the Z-Score, while Book Value of Equity to Book Value of Debt and Sales to Total Asset affect the Z-Score. Overall variable factors model at Altman model revision simultaneously affect the Z-Score. 2) Springate Model (S-Score): Working Capital to Total Asset and EBIT to Total Aset affect S-Score, while Earning Before Tax to Current Liabilities and Sales to Total Asset have no effect on the S-Score. All variables factors at Springate model simultaneously affect the S-Score. The conclusion, the better and more precision model in predicting financial distress based on the Nagelkerke R Square testing, is the Revised Altman (Z-Score) model with a value of 82.5%.